Incredible medical mysteries 2 transsexuals - Hunter, Stephen; Armstrong, Jane; Galligan, Kathryn Liptrott; Ackerley, Paul (Discovery home & health, 2003)
This program tackles the challenges facing the transsexuals. For these people, the issue of gender is an issue of personal identity -- of who they are as a whole person. And that after the change, it will prove that gender is not just a sexual matter, nor a personal one, but that it involves the entire social structures.